665 A Systematic Review of Breast Site Associated Complications Following Deep Inferior Epigastric Perforator (DIEP) Flap Breast Reconstruction. (19th August 2022) - Darling, A; McLaughlin, D; McGarry, K
Abstract: Aim: Breast reconstruction with autologous tissue provides durable reconstruction with native tissue. However, perioperative complications impact negatively on patient perception of success and increase the psychological trauma of mastectomy. The Deep Inferior Epigastric Perforator (DIEP) flap has a recognised low rate of donor site complications. This paper provides the first systematic review focussing on breast site associated complications. Method: PRISMA guidelines informed a systematic search of Medline, Embase and Web of Science. Studies were screened against set inclusion and exclusion criteria; data was collated regarding demographics, flap characteristics and flap complications. Results: Twenty-nine studies representing 21, 680 flaps were included with the rate of major breast-associated complications ranging between 0 and 55.1% of flaps and 0 to 10.3% of patients; the rate of minor complications ranged between 0 and 48.2% of flaps and 0 to 16.3% of patients. All papers reported major complications including total flap loss (1–17.2% flaps, 0–7.4% patients), partial flap loss (0–44.8% flaps, 0–5% patients) and venous congestion or arterial compromise (1.5–55.1% flaps, 4.3–10.3% patients). Twenty-eight papers reported minor complications and included fat necrosis (1.8–48.2% flaps, 3–16.3% patients); wound problems (1–15.6% flaps, 3.7% patients); skin necrosis (9.2–17.8% flaps, 0.3–7.4% patients; seroma (0–4.9% flaps, 0–5.1% patients); haematoma (0.36–9.3% flaps, 0–8.4% patients) and infection (0.2–20% flaps, 0–6.3% patients). Conclusions: This systematic review concludes that the DIEP flap has an acceptable level of breast site associated complications and should continue to be considered as gold standard in breast reconstruction. This review can be used in preoperative counselling and to inform consent.